2010
DOI: 10.1111/j.1365-2869.2010.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation suppresses the increase of rapid eye movement density across sleep cycles

Abstract: We investigated the association between rapid eye movement (REM) density (REMd) and electroencephalogram (EEG) activity during non-rapid eye movement (NREM) and REM sleep, within the re-assessment, in a large sample of normal subjects, of the reduction of oculomotor activity in REM sleep after total sleep deprivation (SD). Coherently with the hypothesis of a role of homeostatic sleep pressure in influencing REMd, a negative correlation between changes in REMd and slow-wave activity (SWA) was expected. A furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…On the one hand, phasic periods are highly activated states with respect to cortical [39,69], mental [40,42] and autonomic activity [116] and resemble active wakefulness. The duration of phasic REM sleep (i.e., REM density) increases towards the end of the night, suggesting that the appearance of phasic periods is facilitated with decreasing homeostatic sleep pressure [117]. Accordingly, sleep deprivation reduces REM density during the recovery night by suppressing the late night increase of phasic periods [117].…”
Section: The Paradoxical Nature Of Phasic and Tonic Remmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, phasic periods are highly activated states with respect to cortical [39,69], mental [40,42] and autonomic activity [116] and resemble active wakefulness. The duration of phasic REM sleep (i.e., REM density) increases towards the end of the night, suggesting that the appearance of phasic periods is facilitated with decreasing homeostatic sleep pressure [117]. Accordingly, sleep deprivation reduces REM density during the recovery night by suppressing the late night increase of phasic periods [117].…”
Section: The Paradoxical Nature Of Phasic and Tonic Remmentioning
confidence: 99%
“…The duration of phasic REM sleep (i.e., REM density) increases towards the end of the night, suggesting that the appearance of phasic periods is facilitated with decreasing homeostatic sleep pressure [117]. Accordingly, sleep deprivation reduces REM density during the recovery night by suppressing the late night increase of phasic periods [117]. REM density is also to some extent modulated by circadian factors, especially in periods of low sleep pressure as revealed by a study applying a forced desynchronization protocol.…”
Section: The Paradoxical Nature Of Phasic and Tonic Remmentioning
confidence: 99%
“…However, above the age of 70 years the opposite is true (Wauquier, 1993). According to Marzano et al (2011), there is no significant difference between the REMD of men and women in their twenties (Marzano et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In connection with sex, different studies obtained different results. On the one hand, Marzano et al (2011) studied men and women in their twenties and found that there is no significant difference between their REMDs. On the other hand, Wauquier (1993) found that REMD changes differently in women and men as they agebetween the ages of 60 and 70 years the REMD of women is higher than that of men, while above the age of 70 years the opposite is true.…”
mentioning
confidence: 99%
“…Marzano and colleagues also conducted a sleep deprivation study and quantified the sleep EEG as well as rapid eye movements during rapid eye movement (REM) sleep (Marzano et al. , 2010).…”
Section: Sleep Deprivation and Rapid Eye Movementsmentioning
confidence: 99%